THE ROLE OF EMOTIONAL INTELLIGENCE AND HUMAN RESOURCES DEVELOPMENT ON EMPLOYEE PERFORMANCE At PT. Prudential Life Insurance Medan Branch - Putra, Ivan Gumilar Sambas; Ma’ruf, Bill; Yustira, Khawari Rama; Oeyliawan, Yohanes; Herawati, Meliana; Juliandini, Savira (CENTRAL ASIA AND THE CAUCASUS, 2022)
The success of an organization is primarily determined by the quality of the people who work in it. The rapidly changing environment demands their ability to capture the phenomenon of change, analyze its impact on the organization and prepare steps to deal with these conditions. This study aims to determine the effect of emotional intelligence and human resource development on employee performance. The data of this study is primary data, namely the data from the questionnaire distributed to 71 respondents. The population in this study were employees at the marketing section of PT Asuransi Jiwa Prudential Medan Branch, as many as 250 employees using the Slovin formula, and obtained a sample of 71 respondents. The analytical method used is multiple regression analysis. The results showed a positive influence of emotional intelligence on employee performance, and there was a positive influence on the development of human resources on the performance of employees of PT Asuransi Jiwa Prudential Medan branch.